2013
DOI: 10.1007/s10916-012-9922-3
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Population-Based Clinical Decision Support to Manage Health and Resource Use for Medicaid Beneficiaries

Abstract: To determine whether a clinical decision support system can favorably impact the delivery of emergency department and hospital services. Randomized clinical trial of three clinical decision support delivery modalities: email messages to care managers (email), printed reports to clinic administrators (report) and letters to patients (letter) conducted among 20,180 Medicaid beneficiaries in Durham County, North Carolina with follow-up through 9 months. Patients in the email group had fewer low-severity emergency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…As illustrated, 61% (22/36) of occurrences of themes identified 7 positive patient medical outcomes as a result of using CDSSs [ 15 , 17 , 20 , 21 , 23 , 26 , 27 , 31 , 32 , 34 , 35 , 37 , 39 , 41 - 48 , 50 ]. Patients experienced improved symptoms [ 20 , 23 , 26 , 41 , 43 , 46 - 48 , 50 ], improved feedback from provider [ 17 , 31 , 42 , 45 ], improved disease management [ 21 , 35 , 37 ], improved efficacy of treatment [ 32 , 39 ], improved screening [ 15 , 27 ], and improved safety [ 34 ], and one study even reported improved mortality [ 44 ]. Although 11 articles did not discuss patient medical outcomes [ 16 , 18 , 19 , 24 , 25 , 28 - 30 , 33 , 40 , 49 ], only 3 reported no statistically significant difference in outcomes between control and intervention groups [ 22 , 36 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As illustrated, 61% (22/36) of occurrences of themes identified 7 positive patient medical outcomes as a result of using CDSSs [ 15 , 17 , 20 , 21 , 23 , 26 , 27 , 31 , 32 , 34 , 35 , 37 , 39 , 41 - 48 , 50 ]. Patients experienced improved symptoms [ 20 , 23 , 26 , 41 , 43 , 46 - 48 , 50 ], improved feedback from provider [ 17 , 31 , 42 , 45 ], improved disease management [ 21 , 35 , 37 ], improved efficacy of treatment [ 32 , 39 ], improved screening [ 15 , 27 ], and improved safety [ 34 ], and one study even reported improved mortality [ 44 ]. Although 11 articles did not discuss patient medical outcomes [ 16 , 18 , 19 , 24 , 25 , 28 - 30 , 33 , 40 , 49 ], only 3 reported no statistically significant difference in outcomes between control and intervention groups [ 22 , 36 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Commensurate with previous reviews on this topic [ 6 , 7 ], a majority of articles analyzed reported improvement in practitioner performance [ 16 - 18 , 21 , 23 - 25 , 28 - 31 , 33 - 35 , 37 , 38 , 40 , 44 , 45 , 47 - 50 ], but contrary to the previous reviews, our review found articles that reported patient outcomes, and a majority were positive outcomes [ 15 , 17 , 20 , 21 , 23 , 26 , 27 , 31 , 32 , 34 , 35 , 37 , 39 , 41 - 48 , 50 ]. Although 9 articles did not discuss practitioner performance [ 15 , 20 , 26 , 27 , 32 , 39 , 41 , 43 ], only 5 articles reported no difference in productivity [ 19 , 22 , 36 , 42 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…risk factors, patient concerns). For the factor CDS to patients versus CDS aimed at the healthcare provider, we point at the findings from one study that found a 14.7% relative increase in the emergency department encounters when computer generated information was directed at the patient versus directed at a healthcare provider [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…As illustrated, 61% (22/36) of occurrences of themes identified 7 positive patient medical outcomes as a result of using CDSSs [15,17,20,21,23,26,27,31,32,34,35,37,39,[41][42][43][44][45][46][47][48]50]. Patients experienced improved symptoms [20,23,26,41,43,[46][47][48]50], improved feedback from provider [17,31,42,45], improved disease management [21,35,37], improved efficacy of treatment [32,39], improved screening [15,27], and improved safety [34], and one study even reported improved mortality [44]. Although 11 articles did not discuss patient medical outcomes [16,18,19,24,…”
Section: Additional Analysismentioning
confidence: 99%